The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1074/jbc.m300054200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Role of a Peroxidase Compound I-type Intermediate in the Oxidation of Glutathione, NADH, Ascorbate, and Dichlorofluorescin by Cytochrome c/H2O2

Abstract: The release of cytochrome c from mitochondria is a crucial step in apoptosis, resulting in the activation of the caspase proteases. A further consequence of cytochrome c release is the enhanced mitochondrial production of superoxide radicals (O 2 . ), which are converted to hydrogen peroxide by manganese-superoxide dismutase. Recently, we showed that cytochrome c is a potent catalyst of 2,7-dichlorofluorescin oxidation to the fluorescent 2,7-dichlorofluorescein by these species, leading to the conclusion that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 74 publications
(62 reference statements)
9
106
0
1
Order By: Relevance
“…Under these conditions HE was totally consumed within 1 h, despite the fact that the concentration of HE was 10 times higher than that of cyt c 3+ . This was attributed to the peroxidase-like activity of cyt c 3+ [19]. Peaks corresponding to products B and C in Figure 3C are proposed as reaction intermediates and A and E + are designated as final products.…”
Section: Characterization Of Products Formed From Cytochrome C-inducementioning
confidence: 93%
See 1 more Smart Citation
“…Under these conditions HE was totally consumed within 1 h, despite the fact that the concentration of HE was 10 times higher than that of cyt c 3+ . This was attributed to the peroxidase-like activity of cyt c 3+ [19]. Peaks corresponding to products B and C in Figure 3C are proposed as reaction intermediates and A and E + are designated as final products.…”
Section: Characterization Of Products Formed From Cytochrome C-inducementioning
confidence: 93%
“…Oxidant-induced iron signaling was shown to be responsible for oxidation of dichlorodihydrofluorescein (DCFH) to a green fluorescent dichlorofluorescein (DCF) product [23]. Mitochondrial cyt c release was reported to catalyze the oxidation of DCFH to DCF [19,23]. Recently, HE-derived red fluorescence was used to monitor the iron-dependent intracellular oxidative events in neuronal cells [24].…”
Section: Ros Detection By Fluorescence Microscopy and Flow Cytometrymentioning
confidence: 99%
“…Third, antioxidants, especially exogenously added antioxidants, greatly affect DCF fluorescence independent of H 2 O 2 levels (153). Most problematic in the use of DCFH for TNF studies is that cytochrome c can act as a peroxidase and oxidize DCFH to DCF, independent of changes to H 2 O 2 levels (18,84). Because cytochrome c is released during TNFinduced apoptosis (when DCF fluorescence is the greatest), DCF oxidation observed after TNF treatment may be a consequence of cytochrome c release that preceded apoptosis rather than changes in H 2 O 2 levels.…”
Section: Dichlorodihydrofluorescein (Dcfh)mentioning
confidence: 99%
“…The evidence about deleterious role of increased SOD1 expression has been most recently complemented by studies demonstrating that overexpression o f S O D 1 i n r e t i n a l e a d s t o i n c r e a s e d hydroperoxide levels and accelerated damage of cone cells (Usui et al, n.d.). The key component for the SOD1-derived hydroperoxide toxicity in IMS is cytochrome c. Previous studies, including electron paramagnetic resonance (EPR) studies (Barr et al, 1996;Svistunenko, 2005;Belikova et al, 2006;Basova et al, 2007) have demonstrated that the reaction of cytochrome c with hydroperoxide results in formation of oxoferryl cytochrome c (peroxidase compound I-type intermediate) and corresponding protein-derived tyrosyl radical, which is highly reactive and has a potential to oxidize proteins, DNA, and lipids, as well as endogenous antioxidants such as glutathione, NADH, and ascorbate (Lawrence et al, 2003) (Fig. 3).…”
Section: Sod1 Catalyzes Increased Hydroperoxide Production In Imsmentioning
confidence: 99%
“…Upon this reaction, hydroperoxide oxidizes the prosthetic heme in the cytochrome c molecule to oxoferryl heme, forming so-called peroxidase compound I-type intermediate, a highly reactive oxidant that is able to react with a number of intracellular targets including proteins, nucleic acids and lipids, causing cell damage (Fig. 3) (Lawrence et al, 2003). Cytochrome c peroxidase activity is controlled by the coordination state of heme iron, particularly by the sulphur ligand of methionine-80 (Met-80), which can be easily displaced by hydroperoxide (Barr et al, 1996;Qian et al, 2002).…”
Section: Sod1 Catalyzes Increased Hydroperoxide Production In Imsmentioning
confidence: 99%